2020
DOI: 10.1002/iub.2402
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited histone deacetylase 3 ameliorates myocardial ischemia–reperfusion injury in a rat model by elevating microRNA‐19a‐3p and reducing cyclin‐dependent kinase 2

Abstract: ObjectiveOver the years, the roles of microRNAs (miRNAs) and histone deacetylase 3 (HDAC3) in human diseases have been investigated. This study focused on the effect of miR‐19a‐3p and HDAC3 in myocardial ischemia–reperfusion (I/R) injury (MIRI) by targeting cyclin‐dependent kinase 2 (CDK2).MethodsThe I/R rat models were established by coronary artery ligation, which were then treated with RGFP966 (an inhibitor of HDAC3), miR‐19a‐3p agomir or antagomir, or silenced CDK2 to explore their roles in the cardiac fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Antioxidant intravitreal injection activated nuclear-factor-E2-related factor 2 (Nrf2) signalling and attenuated retinal dysfunction by light damage in mice, and thus, targeting oxidative stress would be regarded as a therapy for neurodegeneration [ 9 ]. HDAC3 would promote oxidative stress in different diseases, including myocardial ischemia-reperfusion (I/R) injury and spinal cord injury [ 26 , 27 ]. In this study, we demonstrated that HADC3 inhibition could be a potential antioxidative therapy and thus provided us with more knowledge in DR management.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant intravitreal injection activated nuclear-factor-E2-related factor 2 (Nrf2) signalling and attenuated retinal dysfunction by light damage in mice, and thus, targeting oxidative stress would be regarded as a therapy for neurodegeneration [ 9 ]. HDAC3 would promote oxidative stress in different diseases, including myocardial ischemia-reperfusion (I/R) injury and spinal cord injury [ 26 , 27 ]. In this study, we demonstrated that HADC3 inhibition could be a potential antioxidative therapy and thus provided us with more knowledge in DR management.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase 2 (CDK2) is a serine/threonine kinase, of which the abnormal activation is related to MI [ 118 ]. RGFP966, a selective inhibitor of HDAC3, can reduce the CDK2 of the myocardium through increasing miR-19a-3p expression, alleviating oxidative stress and even cardiac injury after MI [ 119 ]. Besides cardiomyocytes, the recruitment and phenotypic differentiation of macrophages are also important for myocardial repair and functional remodeling during MI.…”
Section: The Role Of Hdac3 and Its Inhibitors In Chronic Diseasesmentioning
confidence: 99%
“…It would be interesting to see, if NCoR1 gene silencing could rescue diabetic cardiomyopathy in these mice by inactivating HDAC3 enzymatic activity. Another study found that inhibiting HDAC3 with RGFP966 increased miR-19a-3p and enhanced cardiac function in a rat model of MI/R ( Song et al, 2020 ). In the hearts of rats with streptozotocin (STZ)-induced diabetes, HDAC3 enzymatic activity led to ischemic cardiac damage ( Xie et al, 2014 ; Qiu et al, 2021 ).…”
Section: Heartmentioning
confidence: 99%